Evaluasi Penerapan Good Corporate Governance (GCG) Pada PT Asuransi Jiwasraya (Persero) Medan - Lastrida Simbolon; Indra Muda; Beby Masitho Batubara (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2023)
Good Corporate Governance (GCG) is very important to control the continuity of the company's business in the future, because the implementation of policies is directly related to the implementation of elements of legal compliance and compliance with ethical values. The background of the problem in this thesis is PT Asuransi Jiwasraya (Persero) Medan delaying the payment of the customer's insurance policy. The formulation of the problem in this study, namely how to evaluate the implementation of GCG at PT Asuransi Jiwasraya (Persero) Medan and what are the obstacles to implementing GCG at PT Asuransi Jiwaraya (Persero) Medan. This study aims to evaluate the application of the principles of good corporate governance (GCG) at PT Asuransi Jiwasraya (Persero) Medan. A descriptive approach with qualitative research methods is used by researchers in carrying out this research. The results showed that Asuransi Jiwasraya (Persero) Medan had implemented GCG but its implementation was not optimal, and there were still obstacles in the implementation of GCG. With this research, it can be used as a guide for companies to evaluate the implementation of GCG principles that have been carried out and provide suggestions for companies to optimize the implementation of GCG principles which are considered not yet maximal in their implementation.